Facial Anthropometry: A Reliable Tool for Stature Estimation in Haryanvi Population - Monika Rathee; Jaswinder Kaur; Suresh Kanta Rathee (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Facial anthropometry is a part of cephalometry that involves the measurements of face. Itis very helpful in reconstructive surgery, forensic medicine, orthodontics and to find ethnic differencesby defining various shapes of face. Facial features of every individual are different even in siblings.These features vary according to gender, racial and biological group, ecological and geographical region.Anthropometry can also be used for estimation of stature, where it cannot be measured directly such asspinal or lower limb deformity or any other neuromuscular disorder.So, the present study attempted to findthat is the facial parameters are reliable in estimation of stature in Haryanvi jaat population and also aimsformulate regression equation for estimation of stature in the same.Methods: A sample of total 300 adult Haryanvi jaatsof age group 20 to 60 years was taken for the presentstudy. Out of them 150 were females and 150 weremales. Anthropometric measurements of face and staturewere taken on each subject.Conclusion: All the studied facial parameters showed positive significant correlation with stature (p<0.01)both in males and females So, it can be concluded that facial anthropometry is a reliable tool for statureestimation in Haryanvi population.